Rural India facing the 21st century - "Harriss-White, Barbara" (London, 2004)
Written by an international team of young scholars, 'Rural India Facing the 21st Century' draws together a profound analysis of a broad range of issues to provide a masterly overview of overall rural development. Its highly original methodology and findings will be of considerable interest for development policy.
Keywords: Rural India